ROTATOR CUFF REPAIR IN SHOULDER ARTHROPLASTY WITH REVERSE SHOULDER ARTHROPLASTY - Hristo Gigov; Mancho Kovachev; Simeon Gigov (Peytchinski Publishing, 2024)
This communication aims to present that shoulder arthroplasty has established itself as a treatment method for proximal humerus fractures. The use in clinical practice of the inverted type of shoulder arthroplasty, combined with rotator cuff repair, has expanded the options for surgeons and enabled better clinical outcomes in the treatment of this type of damage. Purpose: Presenting the early results of reverse shoulder endoprosthesis when combined with restoration of the rotator cuff tendons. Material and methods: We present five patients with proximal humerus fractures, in which a humeral reverse endoprosthesis was used, combined with repair and reinsertion of rotator cuff tendons. Results: From the achieved results, the rapid progress in restoring the range of motion in the shoulder joint and the mild limitation of external rotation are impressive, and we rate these early results as very good. Conclusions: We believe that rotator cuff structures restoration is important to ensure the stability of the shoulder joint in reverse shoulder arthroplasty and has a direct relation with the achievement of good clinical results in the early postoperative period.